Enduring stress: A quantitative analysis on coping profiles and sport well-being in amateur endurance athletes. (March 2023) - Rose, Seth; Burton, Damon; Kercher, Vanessa; Grindley, Emma; Richardson, Clarissa
Abstract: Endurance athletes experience physical and psychological stress during training and competition that can inhibit performance and promote negative health implications (i.e., lower well-being) without proper coping mechanisms (McCormick et al., 2018; Sakar & Fletcher, 2014). Additionally, these athletes that train at an amateur level have received limited attention regarding coping with stress and how it impacts well-being (McCormick et al., 2018). The purpose of this study was threefold: to (a) determine common coping profiles of trained amateur endurance athletes, (b) explore the relationship between sport well-being and these coping profiles, and (c) examine the potential roles that appraisals might play in the coping-well-being relationship. The results yielded five distinct coping profiles: Mixed Adaptive Copers (MAC), Mixed Maladaptive Copers (MMC), Engaged Copers (EC), Avoidant Copers (AC), and Social Copers (SC). Coping profiles differed across various variables including sport well-being, appraisals, and demographic factors. Overall, MAC and EC had higher levels of sport well-being. MAC viewed stressors as a challenge (i.e., opportunity) compared to EC and AC. These findings suggest the complex nature of coping in sport and that athletes should develop an assortment of coping strategies that provide different strategies for various stressful situations. Highlights: Coping profiles may optimize understanding of strategies athletes use to manage stress. Copers exuding adaptive behaviors have higher levels of sport well-being. Amateur athletes may utilize social support as a coping outlet for stressors.